Teachers' Creativity in Designing Child-Friendly Digital Mathematics Assignments: A Classroom Implementation Study - Ririn Dwi Agustin; Kenys Fadhilah Zamzam (Universitas Muhammadiyah Malang, 2026)
The rapid advancement of digital technology requires mathematics teachers to design learning experiences that are not only technology-integrated but also meaningful and child-friendly. However, previous studies have primarily examined the impact of teacher creativity on student learning outcomes, with limited attention to how teacher creativity is implemented and developed throughout classroom practice. This study aims to explore the implementation of teachers' creativity in designing Child-Friendly Digital Mathematics Assignments and to develop a Teacher Creativity Implementation Model (TCIM). The study employed an Embedded Mixed Methods design, where qualitative data served as the primary source and quantitative data supported the findings. Participants included junior high school mathematics teachers and students involved in digital mathematics learning. Data were collected through classroom observations, semi-structured interviews, document analysis, digital assignment artifacts, student engagement questionnaires, and Higher Order Thinking Skills (HOTS) tests. Qualitative data were analyzed using an interactive analysis model, while quantitative data were analyzed descriptively. The findings revealed that teachers' creativity develops through a continuous cycle consisting of Need Analysis, Creative Design, Child-Friendly Digital Mathematics Assignments, Classroom Implementation, Student Response, Reflection, Revision, and Enhanced Creativity. The implementation of TCIM fostered more interactive, contextual, and student-centered mathematics learning while enhancing student engagement and supporting higher-order thinking skills. This study contributes a Teacher Creativity Implementation Model (TCIM) that serves as both a conceptual framework and a practical guideline for designing, implementing, and continuously improving child-friendly digital mathematics assignments.